Etiology of Children's Diarrhea in Montevideo, Uruguay: Associated Pathogens and Unusual Isolates - Torres, M. E. (American Society for Microbiology, 2001)
We studied microorganisms associated with infant diarrhea in a group of 256 children admitted to a public pediatric hospital in Montevideo, Uruguay. Diagnostic procedures were updated to optimize detection of potential pathogens, which were found in 63.8% of cases, and to be able to define their characteristics down to molecular or antigenic type. Coinfection with two or more agents was detected in more than one-third of positive studies. Escherichia coli enteric virotypes, especially enteropathogenic E. coli (EPEC), were shown to be prevalent. Rotavirus, Cryptosporidium, Campylobacter (mainly Campylobacter jejuni), and Shigella flexneri were also often identified. Enterotoxigenic E. coli, Salmonella, and Giardia lamblia were sporadically recognized. Unusual findings included two enteroinvasive E. coli strains, one Shigella dysenteriae 2 isolate, and a non-O:1 Vibrio cholerae culture. EPEC bacteria and S. flexneri (but not Salmonella) showed unusually frequent antimicrobial resistance, especially towards beta-lactam antibiotics, which is the subject of ongoing work.